Analisis Potensi dan Strategi Pengembangan Wisata Alam Air Terjun Silimalima di Kabupaten Tapanuli Selatan Analysis of Potential and Development Strategy for Silimalima Waterfall As An Ecotourism on South Tapanuli Regency - Mhd. Rizky Azhari Nasution; Agus Purwoko; Kansih Sri Hartini (Program studi Kehutanan USU, 2016)
Forest resources have so much benefits for human being. One of the example is environmental service such as ecotourism. Silimalima Waterfall is one of the ecotourism that can be found on Simaninggir Village, Marancar Districts, South Tapanuli Regency, North Sumatera Province. This waterfall needs some developments to be ready as an ecotourism that will give some benefits for local communities and to minimize the environmental damage that often caused by the tourism activity. The purpose of the research were to analyze the potential of Silimalima Waterfall and to analyze the problems along with strategies of Silimalima Waterfall development. The research was conducted by giving the questioner about internal and external factors to the respondents, local communities and the employers of Dinas Pemuda Olahraga dan Pariwisata of South Tapanuli Regency. Data results will be used to find the strengths, weaknesses, opportunities and threats of Silimalima Waterfall as an ecotourism on South Tapanuli Regency. The result of this research showed that the feasibility percentage of Silimalima Waterfall development is 73,72%, that makes it feasible to do the developments. The result of SWOT Analysis shows that Silimalilma Waterfall is on the first quadrant that means Siimalima Waterfall is on a very profitable position because the strengths could covers the weaknesses and the threats and also make it possible to take all of the opportunities. Keywords: Potency Analisys, Development strategy, Silimalima Waterfall, feasibility, SWOT analysis